PEMBUATAN SISTEM INFORMASI PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE JOB COSTING PADA PT. X - Suhandi, Sebastian; Adipranata, Rudy; Dewi, Lily Puspa (Jurnal Infra, 2014)
PT. X is a company that engages in the aluminium cargo box assembly. This company assembles and manufactures aluminium cargo box depends on customerâs orders. Inventory, use of raw materials, and cost of goods manufactured are recorded manually. When it comes to determining the cost of goods manufactured, the owner calculates based on the cost of raw materials only, the owner did not pay enough attention to the labour cost and overhead cost. An accurate calculation of cost of goods manufactured is essential since it helps the company to make sure that the determined sales price can cover all the cost incurred. Manual recording could slow down the performance and increase the possibility of inaccurate calculation of cost of goods manufactured.Based on the case, an application to do the calculation of cost of goods manufactured is designed. The process of designing application has gone through several stages, starting from doing survey on the production system, data analyzing, designing Data Flow Diagram and Entity Relationship Diagram of the application. The application uses Microsoft Visual Studio .Net 2005 as its programming language and Microsoft SQL Server 2005 as its database. The calculation of cost of goods manufactured is using Job Costing method.Results that obtained from the application that have been made are raw material usage that can be saved based on Bill of Material or additional in the real process, labour usage, and so on associated with the production process. In addition, the application that has been made can be used to allocate the cost that occurs during the production process and to generate reports related to the calculation of Cost of Goods Manufactured of a product automatically.